TINGKAT KECEMASAN TERHADAP KETIDAKTERATURAN SIKLUS MENSTRUASI PADA SANTRIWATI DI SMA IT DARUL MUKHTARIN TAHUN 2020 - Nuryanah Nuryanah (Nusantara Hasana Journal, 2021)
Anxiety in adolescents is characterized by the emergence of anxiety, anxiety, and the many changes that occur both emotional, physical, changes in self-perception, body shape, psychological changes, even changes in which the reproductive organs start active which is characterized by growing breasts, widening of the pelvis, the presence of hair on the mons pubis (genitals) and armpits, as well as bleeding from the vagina called menstruation. The occurrence of psychological changes in adolescents generally makes the production of reproductive hormones disrupted, causing irregular menstrual cycles. To determine the relationship between anxiety levels and menstrual cycle irregularities. This research is a quantitative study with a descriptive correlational research design with a cross-sectional approach. the population in this study were 100 female students with the technique used in data collection namely total sampling by distributing questionnaire sheets that were valid and reliable. Univariate and bivariate data analysis using the Chi-Square and Correlation test. Based on the Chi-Square test, the P value = (0.014 <0.05).